“Now I’m Not Afraid”: The Influence of Identity-Focused STEM Professional Organizations on the Persistence of Sexual and Gender Minority Undergraduates in STEM - Campbell-Montalvo, Rebecca; Cooke, Hannah; Smith, Chrystal A. S.; Hughes Miller, Michelle; Wao, Hesborn; Puccia, Ellen; Mayberry, Maralee; Skvoretz, John (Frontiers in Education, 2022)
Abstract: In comparison to work on women and historically excluded racial/ethnic minority students in STEM, research on sexual and gender minority (SGM) students in STEM is somewhat incipient. There is little scholarship available on SGM-focused STEM organizations (e.g., oSTEM). Building on the previous literature, we examine how SGM-focused STEM organizations provide social capital, both expressive (e.g., emotional support) and instrumental (e.g., academic resources), that helps students feel they fit in STEM and ultimately persist. We report findings from a large online survey with 477 SGM STEM undergraduates, 463 of whom participate in STEM organizations, which offers one of if not the largest study on the topic to date. We compare three types of identity-focused organizations, SGM-focused, women-focused, and race/ethnicity-focused, finding that they each provide expressive capital to SGM students. The organizations helped students cultivate supportive networks of peers like themselves who then help them feel they fit in STEM through similar but not identical mechanisms. For SGM-focused organizations, their assistance in helping students reconcile their SGM identities with their STEM identity was an important nuance tailored to SGM students’ needs. However, SGM-focused organizations provided less instrumental social capital, which we posit may take a back seat to SGM STEM students’ expressive needs. Unfortunately, women-focused organizations were not always welcoming to SGM students. However, some identity-focused organizations established partnerships with other identity-focused organizations, highlighting the possible role of such collaboration in better serving SGM students, particularly those with minoritized ethnic/racial identities. Implications for research and practice are included.